Propriedades mecânicas das ligas Ti34Cu36Ni8Zr22 e (TiZr)80Co12Fe8 - Medeiros, Marcia Moreira (2012)
Bulk amorphous and nanocrystalline alloys have attracted great interest from the scientific community. Titanium based alloys have demonstrated potential for formation of amorphous. This study aimed at to evaluate the mechanical properties of the Ti34Cu36Ni8Zr22 and (TiZr)80Co12Fe8 alloys, at room temperature. Thereby, nanoindentation, compression and three points bending tests were performed. The methodology involved the following steps: (i) production of alloys by arc melting under argon atmosphere, (ii) production of amorphous ribbon by melt-spinning, (iii) heat treatment of the ribbons at different temperatures, (iv) production of test specimens through casting in copper chill followed by quenching (v) microstructural characterization via scanning electron microscopy (SEM) with energy dispersive spectroscopy (EDS), transmission electron microscopy (TEM), differential scanning calorimetry (DSC) and X-ray diffraction (XRD), (vi) mechanical characterization based on nanoindentation, compression and torsion tests. The results of nanoindentation showed an increase in hardness and reduced Young's modulus as the temperature of the heat treatment approachs the crystallization temperature. Results of compression and bending showed strong dependence on the preparation surface and internal defects of the specimens. The Young's modules and tensile strengths are below those reported in the literature, probably due to internal defects present in the samples such as pores.